The settlement history of Alsónyék–Bátaszék: Complex analysis of its buildings in the context of the Lengyel culture - Osztás, Anett (Dissertationes Archaeologicae, 2021)
Abstract of the PhD thesis submitted in 2019 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Eszter Bánffy.